Tindak Kejahatan Genosida Oleh Myanmar Kepada Etnis Rohingya Ditinjau Dari Perspektif Hukum Pidana Internasional - Siti Nurhaliza; Sulis Setya Damayanti (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The crime of genocide, which is the extermination of a group or cultural background, as well as criminal acts against political groups that are difficult to identify or know, can cause international problems in a country. The crime of genocide under International Criminal Law is considered an extraordinary act and is prohibited. This research uses normative legal research. Information is obtained through literature study, which includes materials such as books, magazines, papers, journals, articles and international agreements. This research aims to determine the factors causing the crime of genocide experienced by the Rohingya ethnic group in Myanmar when viewed from the perspective of International Criminal Law and how to resolve the conflict between the Myanmar government and the Rohingya ethnic group when viewed from the perspective of International Criminal Law. The research results stated that the main cause of the crime of genocide was triggered by political interests. Differences in race, ethnicity and religion. The crime committed by the Myanmar government by the Rohingya Muslim ethnic group is an international crime of genocide, because it fulfills several basic elements, namely mass murder, discrimination against religious minorities, carried out systematically, and aimed at eliminating an ethnic group and a particular group.